Empirically Detecting False Test Alarms Using Association Rules - Herzig, Kim; Nagappan, Nachi (Companion Proceedings of the 37th International Conference on Software Engineering, 2015)
Applying code changes to software systems and testing these code changes can be a complex task that involves many different types of software testing strategies, e.g. system and integration tests. However, not all test failures reported during code integration are hinting towards code defects. Testing large systems such as the Microsoft Windows operating system requires complex test infrastructures, which may lead to test failures caused by faulty tests and test infrastructure issues. Such false test alarms are particular annoying as they raise engineer attention and require manual inspection without providing any benefit. The goal of this work is to use empirical data to minimize the number of false test alarms reported during system and integration testing. To achieve this goal, we use association rule learning to identify patterns among failing test steps that are typically for false test alarms and can be used to automatically classify them. A successful classification of false test alarms is particularly valuable for the product teams as manual test failure inspection is an expensive and time-consuming process that not only costs engineering time and money but also slows down product development. We evaluating our approach on system and integration tests executed during Windows 8.1 and Microsoft Dynamics AX development. Performing more than 10,000 classifications for each product, our model shows a mean precision between 0.85 and 0.90 predicting between 34% and 48% of all false test alarms.